Reliability of the plastic deformation behavior of a Zr-based bulk metallic glass. (July 2016) - Fan, J.J.; Yan, Y.F.; Chen, S.H.; Ng, Chi-Ho; Wu, F.F.; Chan, K.C.
Abstract: It is important to interpret the scattering of the plastic deformation behavior data for the structural-applications of bulk metallic glasses (BMGs), however, few studies have focused on statistical analysis of the variation and reliability of the plastic deformation behavior of BMGs. In this work, statistical analyses show unavoidable large variations in the maximum nominal strains of as-cast BMGs, although they exhibited greatly-enhanced average values of the maximum nominal strains with reduced sample sizes and in the presence of stress gradients. The large variations are attributed to the intrinsic variability of the atomic arrangements stemming from the solidification processes. Nevertheless, the investigations show enhanced cut-off nominal strains (safety threshold) in the specimens with stress gradients. The findings suggest that, despite large variations in the plastic deformation behavior, BMGs are still reliable in practical structural-applications where the materials always deform under more complex stress states. Highlights: Reliability of the plastic deformation behavior of a BMG was investigated. Large variations in the plastic deformation behavior were observed. The large variations are attributed to the intrinsic variability. With stress gradient, an enhanced safety threshold was achieved. BMGs are reliable in practical structural-applications.